Analisis Kualitas Pelayanan Di Bandar Udara Abdul Rachman Saleh Kota Malang - Bima Wahyu Ramadhani; Teguh Ariebowo (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
Air transportation has an important role in providing transportation services for the transportation of people and goods between one airport and another, which is located connecting one country to another by using airplanes through flight routes (flight routes). The role of the airport as an air transportation infrastructure that continues to grow, is not only a symbol of transportation but also a symbol of the economy. The author raises the title of the thesis about "Analysis of Passenger Interests at Abdul Rachman Saleh Airport, Malang City ". This airport is quite interesting to research because it has very minimal flight routes, with only two flight routes. This research uses mixed methods or combination methods which combine quantitative methods and qualitative methods. The type of data used is secondary data. The results of this study cover the quality of service to the interests of passengers at Abdul Rachman Saleh Airport, Malang City, by conducting a trial of a questionnaire instrument that collects 15 questions that are disclosed to 30 respondents. Of the 15 questions, there are 13 valid questionnaire questions and 2 invalid ones.